Structural and socio-cultural barriers to accessing mental healthcare among Syrian refugees and asylum seekers in Switzerland. Issue 1 (31st December 2020) - Kiselev, Nikolai; Pfaltz, Monique; Haas, Florence; Schick, Matthis; Kappen, Marie; Sijbrandij, Marit; De Graaff, Anne M.; Bird, Martha; Hansen, Pernille; Ventevogel, Peter; Fuhr, Daniela C; Schnyder, Ulrich; et al.
ABSTRACT: Background : Due to their experiences of major stressful life events, including post-displacement stressors, refugees and asylum seekers are vulnerable to developing mental health problems. Yet, despite the availability of specialized mental health services in Western European host countries, refugees and asylum seekers display low mental healthcare utilization. Objective : The aim of this study was to explore structural and socio-cultural barriers to accessing mental healthcare among Syrian refugees and asylum seekers in Switzerland. Method : In this qualitative study, key-informant (KI) interviews with Syrian refugees and asylum seekers, Swiss healthcare providers and other stakeholders (e.g. refugee coordinators or leaders) were conducted in the German-speaking part of Switzerland. Participants were recruited using snowball sampling. Interviews were audiotaped and transcribed, and then analysed using thematic analysis, combining deductive and inductive coding. Results : Findings show that Syrian refugees and asylum seekers face multiple structural and socio-cultural barriers, with socio-cultural barriers being perceived as more pronounced. Syrian key informants, healthcare providers, and other stakeholders identified language, gatekeeper-associated problems, lack of resources, lack of awareness, fear of stigma and a mismatch between the local health system and perceived needs of Syrian refugees and asylum seekers as key barriers to accessing care. Conclusions : The results show that for Syrian refugees and asylum seekers in Switzerland several barriers exist. This is in line with previous findings. A possible solution for the current situation might be to increase the agility of the service system in general and to improve the willingness to embrace innovative paths, rather than adapting mental healthcare services regarding single barriers and needs of a new target population.